Biological activity of natural sesquiterpenoids containing a gem-dimethylcyclopropane unit1. Issue 8 (22nd August 2015) - Durán-Peña, María Jesús; Botubol Ares, José Manuel; Hanson, James R.; Collado, Isidro G.; Hernández-Galán, Rosario
<x xml:space="preserve">Abstract</x> The biological activity of sesquiterpenes containing the gem-dimethylcyclopropane unit is described.